Penicillin in Borrelia burgdorferi-negative Primary Cutaneous Marginal Zone Lymphoma: A Case Series and Literature Review - Yao Qin; Yang Wang (Acta Dermato-Venereologica, 2022)
Abstract is missing (Short communication)